2012
DOI: 10.1097/paf.0b013e3182557dcf
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Abscess Presenting a Very Rapid Progression

Abstract: Pituitary abscess is a rare disease presenting with nonspecific clinical symptoms, and diagnosis is often difficult. This disease is potentially life-threatening, but most cases have a chronic and indolent course. We report a case of a 60-year-old man with a pituitary abscess associated with pituitary adenoma who died 5 days after the onset of clinical symptoms without a definitive diagnosis. Postmortem computed tomography and autopsy findings revealed a sellar mass with cystic change and extension toward the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
0
8
0
1
Order By: Relevance
“…Complete recovery rate was around 60% in patients where adequate treatment was administered, while 30% of patients showed incomplete recovery with visual or endocrine impairment 2,10 . However, lethal outcomes have also been reported 1 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Complete recovery rate was around 60% in patients where adequate treatment was administered, while 30% of patients showed incomplete recovery with visual or endocrine impairment 2,10 . However, lethal outcomes have also been reported 1 .…”
Section: Discussionmentioning
confidence: 97%
“…Clinical presentation is rather nonspecifi c, ranging from acute to chronic or even indolent course 1 . Hematogenous spread, or direct extension from an infected neighboring tissue, in conditions such as paranasal sinusitis, sepsis, meningitis, cavernous sinus thrombophlebitis, pituitary surgery and tooth infection, are the main risk factors for this disease 2,3 .…”
Section: Introductionmentioning
confidence: 99%
“…The infection can also originate in a pituitary gland with preexisting pathology, with a pituitary adenoma being the most common associated lesion followed by craniopharyngioma and Rathke's cleft cyst (8,10). Regarding the pediatric cases, only 27% (3/11) of the patients had an underlying pituitary gland condition.…”
Section: Discussionmentioning
confidence: 97%
“…Although this disease most commonly has an indolent presentation, a rapid progressive clinical picture with fatal outcome has also been described (8).…”
Section: Discussionmentioning
confidence: 98%
“…Kotani et al reported a 60-year-old man with a pituitary abscess associated with a pituitary adenoma who died five days after the onset of clinical symptoms without a definitive diagnosis (65). Postmortem imaging and autopsy findings revealed a sellar mass with cystic change and extension toward the optic chiasm.…”
Section: Pituitary Abscessmentioning
confidence: 99%